Phenotypic Characterization of a Virulent PRRSV-1 Isolate in a Reproductive Model With and Without Prior Heterologous Modified Live PRRSV-1 Vaccination - Kreutzmann, Heinrich; Stadler, Julia; Knecht, Christian; Sassu, Elena L.; Ruczizka, Ursula; Zablotski, Yury; Vatzia, Eleni; Balka, Gyula; Zaruba, Marianne; Chen, Hann-Wei; Riedel, Christiane; Rümenapf, Till; et al. (Frontiers in Veterinary Science, 2022)
Reproductive disorders induced by porcine reproductive and respiratory syndrome virus (PRRSV) cause high economic losses in the pig industry worldwide. In this study we aimed to phenotypically characterize a virulent PRRSV-1 subtype 1 isolate (AUT15-33) in a reproductive model. Furthermore, the protective effect of a heterologous modified live virus vaccine (ReproCyc® PRRS EU) was evaluated. In addition, PRRSV AUT15-33 was genotypically compared to other well-characterized isolates. Sixteen gilts were equally divided into four groups: a vaccinated and infected (V-I), a vaccinated and non-infected (V-NI), a non-vaccinated and infected (NV-I), and a non-vaccinated and non-infected (NV-NI) group. After PRRSV infection on gestation day 84, all gilts were clinically examined on a daily basis and blood samples were taken at five time points. Necropsy was performed three weeks after infection. The fetal preservation status was assessed and PRRSV RNA concentrations were measured in blood and tissue samples from all gilts and fetuses. After infection, all four gilts in the NV-I group were viremic throughout 17 days post-infection (dpi), whereas two gilts in the V-I group were viremic at only one time point at 6 dpi. Viral load was significantly higher in gilt serum, tracheobronchial lymph nodes, uterine lymph nodes, maternal endometrium, and fetal placenta of NV-I gilts compared to the V-I ones (p < 0.05). Moreover, the preservation status of the fetuses derived from NV-I gilts was significantly impaired (55.9% of viable fetuses) compared to the other groups (p < 0.001). Upon comparison with other known isolates, phylogenetic analyses revealed the closest relation to a well-characterized PRRSV-1 subtype 1 field isolate from Belgium. In conclusion, the high virulence of AUT15-33 was phenotypically confirmed in an experimental reproductive model. The vaccination of the sows showed promising results in reducing viremia, fetal damage, and transplacental transmission of the PRRSV-1 strain characterized in this study.